Real-time mapping of the subepithelial nerve plexus by in vivo confocal laser scanning microscopy. Issue 9 (2nd September 2010) - Zhivov, Andrey; Blum, Marcus; Guthoff, Rudolf; Stachs, Oliver
Abstract : Aim: To produce two-dimensional reconstruction maps of the subepithelial nerve plexus (SEP) in living cornea by in vivo laser scanning confocal microscopy in real time. Methods: In vivo confocal laser scanning microscopy (Heidelberg Retinal Tomograph II in conjunction with the Rostock Cornea Module) was performed on normal eyes (n=6) and eyes after laser-assisted in situ keratomileusis (LASIK) (n=4). Source data (frame rate 30 Hz) were used to create large-scale maps of the scanned area in Automatic Real Time composite mode. The algorithm aligns single live images onto the previously mapped composite image using landmark feature-based image processing. Results: Real-time mapping of the SEP was performed on a large-scale area up to 3.2×3.2 mm (3072×3072 pixels) in healthy subjects and in post-LASIK patients. Two-dimensional structures of the SEP were imaged in all 10 eyes. Mapping quality as well as acquisition time were dependent on subject compliance and examiner experience. Conclusion: The described method permits real-time in vivo mapping of the SEP, thus providing the necessary basis for statistically robust conclusions concerning morphometric plexus alterations.